Impatiens arunachalensis (Balsaminaceae), a new species from northeastern India - Hareesh, Vadakkoot Sankaran; Joe, Alfred; Gogoi, Rajib; Sabu, Mamiyil (Phytotaxa, 2017)
Impatiens arunachalensis, a new species of Impatiens is described from the Upper Siang district of Arunachal Pradesh, northeast India. Detailed descriptions, distribution, and discussion of ecology along with colour photographs are provided.